Wine, Rice, or Both?: Overwriting Sectarian Strife in the Tendai Shuhanron Debate - Watanabe, Takeshi (Japanese journal of religious studies, 2009)
This article examines the Shuhanron emaki (The illustrated scroll of the wine and rice debate) as not only a reflection of late Muromachi-period cultural trends, but also a reworking of its sixteenth-century historical setting. The work ostensibly features three men who each argue their various positions: one extolling wine, the other rice, and the third a balance of both. Yet its references to the Lotus school (also the Hokke or Nichiren school), the Nenbutsu school (the True Pure Land school), and the supremacy of the Tendai school with its belief in the Three Truths and the Middle Way, point to the Tenbun Hokke Uprising of 1536. This conflict featured these three religious parties in brutal violence that devastated the capital, already ravaged by famines and unending warfare. In playfully representing a Utopian, yet realistic world full of food and merriment, the makers of this work urge sectarian reconciliation by showing what peace could potentially bring.